My monster truck family - Cena, John; Aikins, Dave; McWilliam, Howard 1977- (New York Random House, 2020)
"Meet Elbow Grease and his brothers. They are a family of monster trucks!"--Page 4 of cover
English Stories
F&P text level G
Preschool-Kindergarten
Keywords: Brothers -- Fiction; Monster trucks -- Fiction; JUVENILE FICTION -- Family -- General; JUVENILE FICTION -- Transportation -- Cars & Trucks; Picture books; Readers (Publications)